30-year cone production dynamics in Siberian stone pine (Pinus sibirica) in the southern boreal zone: a causal interpretation - Sergey Goroshkevich; Svetlana Velisevich; Aleksandr Popov; Oleg Khutornoy; Galina Vasilyeva (Plant Ecology and Evolution, 2021)
Background and aims – Siberian stone pine is a keystone species for Siberia, and numerous studies have analyzed Siberian stone pine seeding dynamics in connection with the dynamics of weather conditions. However, all studies were based on observations before 1990. The aim of the study was to expand our knowledge about the balance of weather and climatic factors in the regulation of cone production to enable conclusions about the current reproductive function in Siberian stone pine.Material and methods – We monitored Siberian stone pine cone production in the southeastern region of the Western Siberian Plain, in association with climatic factors, over a period of 30 years. To analyze the relationship with weather conditions, we used the trait mature cone number per tree and weather data obtained from the weather station in Tomsk.Key results – During this period, cone production decreased by about one-third, mainly caused by the complete absence of high yields. The main factor negatively affecting cone production was late spring frost: severe frost occurring with a large accumulated sum of effective temperatures resulted in full cone loss, and light frost substantially reduced cone number. A less important but significant climatic factor was September temperature: as the temperature increased, the cone number decreased in the following year. Over the last 30 years, the sum of the effective temperatures at which the last spring frost occurs, as well as the average September temperature, increased considerably, resulting in reduced cone production.Conclusion – If the current climatic trend is maintained, and especially if it is strengthened, Siberian stone pine cone production in the southern boreal forest zone on the Western Siberian Plane is unlikely to provide for the effective renewal of the species.